Language Maintenance and Shift in Diraytata - Melaku, Zelalem; Semu, Sintayehu (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2023)
Language maintenance and shift are common words that show once language whether transfer from one generation to the other by keeping the cultural aspects of the native speakers or losing the content and form of the language. Therefore, the existence of language indeed cannot be separated from our day-to-day life. However, the interaction between one person and another can deliver different messages smoothly in their mother tongue language. This study was focused on language maintenance and shift in Ethiopia in the case of the Diraytata language. The researchers collected sufficient data by using interviews, questionary and group discussions. After collecting data concerning language maintenance and shift in Diraytata and interpreting by the qualitative method. Regarding sampling technique, purposeful sampling was implemented. Finally, the finding shows that in the Diraytata language, speakers constantly use their mother tongue for day-to-day communication, church bible learning, and teaching. In primary school, 1-4 class is given as one subject, local elders used for negotiation, in social life like equb, idir, mahiber and cultural beverage setting like cheqa and tella. All listed above positively impact language maintenance activities performed by Diraytata speakers. In addition, individuals, families, government, and private sectors collaborated for the language maintenance of Diraytata for the next generation. On the other hand, key informants described that marriage out of Derashe ethnic groups might lead to a language shift. It is because of Brive price for females. Males in Derashe ethnic groups who want to marry their own ethnic must ask to pay a high amount of Brive price for females. Therefore, males decided to marry out of their ethnic groups and pay some Brive price for females or for free. At this time, the two different ethnic groups lived together, and the new child mixed language and culture. So, the child preferred to engage mother language, and it missed their father’s language and culture. However, language shifts may occur during the time of exogamy marriage.